2022
DOI: 10.1038/s41598-022-17591-4
|View full text |Cite
|
Sign up to set email alerts
|

Advanced separation and classification of ionospheric troughs in midnight conditions

Abstract: This study uses a novel approach to separate and classify different ionospheric troughs from CHAMP satellite data in the winter midnight ionosphere of the southern hemisphere at high solar activity (2000–2002). The main ionospheric trough (MIT) was separated from the high latitude trough (HLT). The separation was performed through an analysis of troughs in the frame of a model of the diffuse auroral particle precipitation. Two types of HLT were distinguished. In the mid-latitude ionosphere, the MIT was separat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…This observation is consistent with the coincidence of the epochs of plasma density and velocity. All the trough events that we examined are characterized by high plasma velocity, and therefore, these events belong to high-latitude trough 2 (HLT2), following the classification by Karpachev (2022aKarpachev ( , 2022b. Electron outflow (or downward FAC) may contribute to the development of high-latitude troughs, but high-speed plasma convection is considered to play the primary role because troughs are detected even in the absence of downward FAC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation is consistent with the coincidence of the epochs of plasma density and velocity. All the trough events that we examined are characterized by high plasma velocity, and therefore, these events belong to high-latitude trough 2 (HLT2), following the classification by Karpachev (2022aKarpachev ( , 2022b. Electron outflow (or downward FAC) may contribute to the development of high-latitude troughs, but high-speed plasma convection is considered to play the primary role because troughs are detected even in the absence of downward FAC.…”
Section: Discussionmentioning
confidence: 99%
“…However, the formation of sharp boundaries of high-latitude troughs required an additional process, and Grebowsky et al (1983) suggested the trough formation by the enhanced dissociative recombination rate associated with high-speed plasma convection. Recent studies (Karpachev, 2022a(Karpachev, , 2022b(Karpachev, , 2023, investigated the conditions for the development of high-latitude troughs under midnight, morning, evening, and noon conditions using the electron concentration data from the Challenging Minisatellite Payload (CHAMP) satellite. Following these studies, two types of high-latitude troughs develop.…”
Section: Introductionmentioning
confidence: 99%
“…This article continues a series of studies on the irregular structure of the winter high-latitude ionosphere [1][2][3]. The main purpose of these studies is the separation and classification of ionospheric troughs.…”
Section: Introductionmentioning
confidence: 94%
“…In addition, there are various types of mid-latitude quasi-troughs. Within the framework of this task, the structures of the midnight ionosphere [1], the early morning and evening ionosphere [2], and the late morning ionosphere [3] were studied in detail. The study was performed using an advanced method based on a simple visual model of the auroral oval [8].…”
Section: Introductionmentioning
confidence: 99%
“…It was the time of many discoveries concerning the ionosphere, especially its structure (equatorial anomaly, main ionospheric trough etс.) [3][4][5][6].…”
mentioning
confidence: 99%